Kajian Distribusi Aliran Intake ke PLTMH Akibat Perubahan Aliran di Hulu Sungai - - Sufrizaliansyah; Muhammad Ilham Maulana (Jurnal Teknik Mesin Unsyiah, 2013)
Micro hydro Power (MHP) Rampah planned to power as many as 95 heads of house holds with an installed power capacity of 20 kW. Source water comes from rivers by building dams Rampah intake. Intake should be on the basis of a steady stream, so it does not impede the flow of water entering the intake. The writing is focused on the stability of the river going up stream along the 300 m intake, based on the difference between the two cross-sectional sediment capacity in each pias. Stream flow that occurred during measurements of 5.724 m3/sec. Debit is used to drive a 50% of the measured discharge, so the available flow is 2.862 m3/sec. This exceeds the initial survey of potential discharge stream Rampah required to drive the turbine at MHP Rampah of 1.5 m3/sec. Calculation of sediment using Frylink method. Turns on up stream erosion, so that down stream erosion, while experiencing the process of deposition of sediment down stream. Debit dominant flooding that occurred in September 2011 until February 2012 amounted to 9.833 m3/sec and a maximum flood discharge of 19.572 m3/sec. While the discharge monitoring using arc discharge regression equation Q = (3.142 H - 0.289)2. In the circumstances the magnitude of dominant flood sediments (bed load) that settles and into the intake tract of 0.00019 m3/sec, while in a state of maximum flood 0.00035 m3/sec. Minimum grain diameter (smallest) as the protector of the river at flood dominant at 21.50 mm, and maximum flood conditions used by 31.00 mm.